Effects of intra-set rest on the ability to repeat work at maximal isometric strength - Garcia-Manso, J. M.; Valverde, T.; Arrones, L.; Navarro-Valdivielso, M.; Martin Dantas, E. H.; da Silva-Grigoletto, M. E. (The Journal of Sports Medicine and Physical Fitness, 2016)
To analyze how the rest between interval repetitions in intra-set training (at maximal isometric loads) could affect the ability to repeat maximal contractions in subjects with different levels of performance and different experience in strength development work. Twenty subjects were divided randomly into two different groups depending on their sport characteristics: ten subjects were trained in strength development work (Group Strenght - 23.1±4.6 years; 172.0±5.3 cm; 79.9±12.1 kg; 2175.6±490.8 N; 46.9±4.9 ml/kg.min), and ten subjects were trained in endurance work (Group Endurance- 21.3±4.5 years; 172.4±4.1 cm; 60.0±4.6 kg; 815.5±206.5 N; 67.4±4.9 ml/kg.min). To assess the ability to repeat maximal efforts, 20 repetitions of 5 sec were performed in a half--squat position, with 1 minute of rest between repetitions. For both groups, four different phases were observed in the Interval Maximal Force test during the 20--repetition assessment: potentiation, maintenance, moderate loss, and significant loss. For the GE, the loss in maximum strength capacity began in the fourth repetition (GS 4th : 3.4%, ns, Effect Size: 0.09 vs. GE 3th : 1.6%; ns; ES: 0.06) and reached a statistically significant value in the twelfth repetition (GS 12th : 12.7%, p: 0.03, ES: 0.35 vs. GE 7th : 12.5%; p=0.01; ES: 0.49). The number of repetitions at which the strength began to decrease depended on the subject's sport characteristic and performance level. This study shows how an appropriate intra-set rest inclusion can significantly increase the work performed in every set without changing the muscle contraction characteristics, thus delaying muscle fatigue and maintaining the desired training objective.